Regeneration Design Study Based on Long-lasting Building Strategy of Typical Chinese Work-live Unit in Guangzhou, China. Issue 4 (1st November 2022) - Wang, Q; Shen, K; Xu, M C
Abstract: After rapid urbanization from last several decades, Pearl River Delta area (PRD) in China gradually steps into an urban regeneration process, especially in the field of housing sector. However, neighbour and housing reform activities in last few years focused on the inner prat of the cities where are mainly historical districts or chaotic urban villages. While another large proportion of housing in "Dan Wei" has been ignored. It is a typical Chinese working unit combined with living and other activities, but currently faces new challenges of social and functional transformation. Although a new regeneration design strategy: "Micro-upgrading", was firstly proposed in Guangzhou and specific for this neighborhood typology, it still cannot ideally resolve its core negative issues in last few years. Therefore, based on an architectural school's design course, this study will select a region concentrated of "Dan Wei" units in Guangzhou, which is the core city of PRD. By making use of "Open Building" theory and "Level" strategy, some valuable research outcomes and design solutions will be discussed and proposed.